A study in environmental chemistry: natural and anthropogenic radionuclides in sediment cores from the Norwegian Trench and the Vefsnfjord - Helvik, Lena (The University of Bergen, 2020)
In this work the anthropogenic radionuclide Cs-137 and the naturally occurring radionuclides Ra-226, Ra-228, Pb-210 and K-40 have been studied in sediment cores from the Norwegian Trench and from the Vefsnfjord in Nordland. Caesium-137 is a fission product, introduced to the environment by nuclear weapons tests in 1950s and -60s, discharges from reprocessing plants for spent nuclear fuel, and from accidents like the Chernobyl accident in 1986. Levels of Cs-137 in Norwegian marine areas are generally low, and the levels are routinely monitored. Investigations in selected Norwegian fjords have, however, shown elevated levels of Cs-137 in surface sediments and sediment profiles, compared to adjacent open marine areas. The Vefsnfjord, which is investigated in this work, is one of the fjords in Norway with the highest measured levels of Cs-137. The contamination source is most likely the Chernobyl accident. Potassium-40 is a naturally occurring radioactive isotope of potassium (isotopic abundance of 0.012%). Radium-226 and lead-210 are members of the natural radioactive “uranium series”, while radium-228 is member of the natural radioactive “thorium series”. All four are found in various amounts in bedrock and the marine environment. However, it is well known that different industries, including the oil and gas industry, also discharge naturally occurring radionuclides to the marine environment. In this thesis, local and regional variations of Cs-137, Ra-226, Ra-228, Pb-210 and K-40 in the two study areas have been investigated. Such information is important when monitoring results are to be interpreted, as monitoring results often are thought to represent a large area. Results from analyses of the different radionuclides in sediment cores taken within an area of 30x30 cm were generally in good agreement with regards to activity concentration, both in the Norwegian Trench and in the Vefsnfjord. Some regional variations between the different sampling locations in the Vefsnfjord were, however, found. The Cs-137 in the ...